(untitled) (EDUCATION IN THE 21ST CENTURY, 2025)
Education has always been and continues to be a key driving force for the development of society. It provides an opportunity to shape generations that are ready to respond to various life challenges and solve them. Even now, when educational systems are refining their structure and developing with the help of new technologies and approaches, the methods of assessing education and their effectiveness have become an important topic of discussion. The article presents innovative methods that contribute to the efficiency of knowledge assessment. Relevance of the article. Modern educational systems constantly require new approaches, particularly in matters of assessing students’ knowledge. The effectiveness of the future educational process primarily depends on the correct choice of methods for assessing residual knowledge, which will help lay a more solid foundation for mastering the learning material, create new opportunities for students’ development, and maximize the effectiveness of educational and upbringing activities. Scientific novelty. The scientific novelty of the article lies in the introduction of innovative methods for assessing residual knowledge. Through an analysis of some features of these methods and their applicability, new approaches are proposed that will allow for more effective and comprehensive assessment of students’ knowledge, skills, and abilities. Relevance of the topic. The topic is relevant because the effectiveness of the educational system largely depends on the continuous improvement of assessment methods. In the context of reforms in general education, the importance of assessing residual knowledge becomes a key issue. The article presents innovative approaches that are significant for the possible continuation of the development of the educational process. Main problems. One of the main issues regarding the limited capabilities of traditional assessment methods is that these methods do not provide a full check of knowledge acquisition and its applicability. In other words, the assessment of learning outcomes does not meet the demands of the time. The introduction of new approaches and technologies requires additional development and retraining of teachers, as well as enhancing their knowledge and skills. Purpose of the article. The purpose of the article is to investigate and analyze the state of assessing residual knowledge using innovative methods, to present their significance and possible applications, which can have a significant impact on the educational process. Novelty lies in the following: The article presents methods and technologies that not only meet modern educational requirements but also complement traditional approaches to assessing students’ knowledge. Practical significance of the study. The study is valuable because it can guide teachers in more effectively applying innovative methods and help improve teaching and assessment processes. Such approaches contribute to improving educational outcomes while providing students with new opportunities for the correct application of residual knowledge.